Effect of project-based learning and problem-based learning on the students' writing achievement - Cahyaningrum, Tri; Widyantoro, Agus (LingTera, 2020)
The objective of the research is to find out significant differences on the writing achievement between students taught through Project-Based Learning, Problem-Based Learning, and those who are not. This research is quasi-experimental research. The subjects consisted of two groups of students as the experimental groups and one group as the control group. The data were obtained by essay writing tests. The data analysis used descriptive analysis and inferential statistics. The hypothesis was tested using the analysis of covariance (ANCOVA) at the significance level of 0.05. The result of the ANCOVA in the posttest score shows that the significance value is 0.001, which is less than the significance level of 0.05 (F = 7.493, p < 0.05). This means that there is a significant difference in the writing ability among grade eight students of SMP N 2 Kalasan taught by using the Project-Based Learning, from those taught using the Problem-Based Learning and those who are not.